Angiographic Findings in the Tolosa–Hunt Syndrome and Resolution after Corticosteroid Treatment. (4th May 2018) - Ravindran, Krishnan; Schmalz, Philip; Torun, Nurhan; Ronthal, Michael; Chang, Yu-Ming; Thomas, Ajith J.
ABSTRACT: The Tolosa–Hunt syndrome is a rare clinical condition characterized by painful opthalmoparesis associated with idiopathic granulomatous inflammation of the orbital apex and cavernous sinus. Historically, this condition was thought to result from arteritic changes in the internal carotid artery and cavernous sinus. Modern digital angiographic techniques were unavailable when THS was initially described, and few reports exist on its high-resolution angiographic findings. Painful ophthalmoparesis, especially of the oculomotor nerve, warrants vascular imaging because of the concern for an underlying aneurysm. Here, we describe angiographic findings of THS which may be useful for clinicians when encountering patients presenting with painful ophthalmoplegia.